Wireless arm-worn bioimpedance sensor for continuous assessment of whole-body hydration - Matija Jankovic; Seungmin Kang; Sarnab Bhattacharya; Jordon Kashanchi; Jieting Wang; Kanika Deoli; Tianda Huang; Alex Johnson; Karina Ambani; Sangjun Kim; Pulin Wang; Edward Coyle; et al. (Proceedings of the National Academy of Sciences, 2025)
Assessment of whole-body hydration (WBH) is crucial for health management and disease diagnosis. Traditional methods are invasive or require bulky equipment, making them impractical for mobile, continuous sensing. We present a wearable bioimpedance sensor with strategic electrode placement across the arm for noninvasive, continuous, and mobile WBH monitoring. Although whole-body bioimpedance is a proven method for indicating WBH, the effectiveness of local bioimpedance measurement has been unclear. Our finite element analysis demonstrated that with an optimized cross-arm sensing configuration, a strong linear relationship exists between arm bioimpedance and muscle electrical resistivity, confirming the utility of arm bioimpedance for assessing WBH given the well-established relationship between muscle electrical resistivity and body water. Our IRB-approved diuretic-induced dehydration study demonstrated a strong linear correlation between the increase of arm bioimpedance and the decrease in body weight due to water loss, with a Pearson correlation coefficient of 0.956 ± 0.033 among eight participants. Arm and whole-body demonstrated strong alignment, suggesting that arm bioimpedance measurements can reflect not only changes in WBH but also potentially absolute WBH status when compared against established population reference data. In a 24-h free-living experiment, the wireless, dry electrode-based, arm-conformable bioimpedance sensor continuously tracked dehydration and rehydration despite motions associated with daily activities. These results suggest that properly measured arm bioimpedance can serve as a surrogate for WBH, offering a reliable and accessible solution. The potential uses of this wearable technology range from improving personal wellness to enhancing professional sports and occupational safety.